Investigating the Impact of Resilience on Learners’ Motivated Behavior of L2 and Proficiency in English of University Students at Karachi, Pakistan - Imran Khan Mahesar; Amjad Ali Jokhio (Universitas Cokroaminoto Palopo, 2021)
This research article investigates the resilience and its various constituting factors and their subsequent relation with Motivated L2 Learning Behavior and English Proficiency among the first year students of two public sector universities of Pakistan. For this quantitative and variables oriented study 260 students were conveniently selected who participated in the study, out of which 152 and 108 were males and females respectively. For data collection of this quantitative study, a five point likert scale Questionnaire ranging from Strongly Disagree to Strongly Agree was employed. The questionnaire comprised 31 items which were further distributed in five dimensions of Resilience (Perceived Happiness, Empathy, Sociability, Persistence and Self Regulation) and Motivated L2 Learning Behaviour as 26 and 05 respectively in order to determine the students’ resilience and L2 Motivated Behaviour. Michigan English Language Assessment Battery (MELAB) test was also conducted in order to measure the English proficiency skills of the students. Moreover, the correlation among the independent and dependent variables and the impact of resilience factors on Motivated L2 Behaviour and English Proficiency was analyzed with the help of standard regression analysis. The results revealed that the four dimensions of resilience significantly influenced Motivated L2 Learning Behaviour whereas; three factors of resilience affected English Proficiency as well. The study can help in understanding the concept of resilience and can be applied to other academic disciplines.